Decision of Queuing Models and Layout Design at a Gas Station - Ika Nurul Qamari; Salma Ayudhona Trizula (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objectives: This study aims to analyze the accuracy of the queuing models and the application of layout design at the gas station in Ngasinan Wonosobo, Indonesia. Fuel service providers are encouraged to optimize service space as the number of motorized vehicle customers grows. The focus of attention in gas station management is not only on the queuing model, but also on the layout design that is acceptable and adequate for customers, particularly motorcycle riders who use Pertalite. This study will look at how to simulate a realistic gas station queue and provide a user-friendly layout design for anyone interested in gas stations.Methodology: The object of this study was a motorcyclist who was doing Pertalite refueling. The types of data used are quantitative and qualitative data, so this study is classified as mixed methods. Purposive sampling was utilized as the sampling method in this study, which is a non-probability sampling strategy. The analytical method used is descriptive analysis and analysis of the Multi-channel-Single phase (M/M/S) queuing model.Finding: The findings of this study indicate that long queues can interfere with the activities of other facility users for other customers at the gas station. This study identifies the need for a neat layout design for motorcycle queues by utilizing the service-scape gas station.Conclusion: Although the queue system performs well in the afternoon, the results of the queuing analysis show that the total length of vehicles in the system does not exceed the length of the line, ensuring that the queue does not obstruct other vehicle paths. Recommendations and study findings are explored as a queuing model and layout design in the future.